Judicial custody of bankrupt bankers - امين خالص نافع; محمد اسماء عبد (Journal of Legal Sciences, 2021)
The management of funds for banks whose bankruptcy is declared and maintained is necessary, as it is a measure that aims primarily to preserve those funds for fear of being smuggled or destroyed, and that constitutes a guarantee of the rights of bank creditors. In his choice to do that task and this person is called in the Iraqi banking law (the judicial guard), which this research was devoted to touch on what is guarding and who is the judicial guard in relation to Iraqi law and other comparative laws and is represented (Lebanese law and Omani law) where the first topic was devoted to a concept to guard Judicial and the appointment mechanism As for the second topic, it has been devoted to talking about the tasks undertaken by the judicial guard and whose importance the law requires the appointment of a person to carry out, knowing that judicial custody as a term implied many differences, both in relation to the banking law and the general provisions of bankruptcy in the Iraqi Trade Law or in relation to For designations adopted by comparative legislation to indicate the meaning of this entity as well as exit from Searching the results that were reached in addition to the mentioned recommendations.